Proximity of the maxillary dentition to the incisive canal and greater palatine foramen among patients with various vertical and sagittal growth patterns - Shakeel, Zainab; Waqar Jeelani,; Maheen Ahmed,; Abdul Muqeet Chughtai, (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the proximity of incisive canal and greater palatine foramen to the maxillary dentition in different vertical and sagittal growth patterns. Method: The cross-sectional study was conducted at the Department of Orthodontics, Bakhtawar Amin Medical and Dental hospital, Multan, from January 15 to June 15, 2024, and comprised cone-beam computed tomography images of adult patients of either gender aged 16-65 years with natural permanent dentition. The subjects were assessed based on both vertical and sagittal lines based on maxillary mandibular angle and Wits appraisal, respectively. The shortest distance from the incisive canal to maxillary incisors, and greater palatine foramen to the nearest molar was determined on axial cross-section. The mean distances were compared between males and females. The mean distances among the vertical (low, normal and high) and sagittal (Class I, II and III) groups were also compared. Data was analysed using SPSS 25. Results: Of the 112 patients with mean age 34.7±11.5 years, 59(52.7%) were females and 53(47.3%) were males. In females, the distance from greater palatine foramen to the nearest molar and the distance from incisive canal to the root apex of right maxillary incisors was found to be increased compared to males (p<0.001). In the vertical group, subjects with normal angle showed the greatest distance from incisive canal to the root apex of right maxillary incisors (p=0.03) and from the right greater palatine foramen to the nearest molar (p<0.001). The distance from incisive canal to the root apex of left maxillary incisors was found to be greatest in Class I subjects (p<0.03). Conclusion: Females, normal-angle and Class I subjects showed a trend towards increased distance between the palatine structures and maxillary dentition. Key Words: Cone-beam computed tomography, Tooth apex, Root resorption, Orthodontic tooth movement, Palatine bone, Mini dental implant.